الثنائية الضدية في قصص حيدر حيدر ((ثنائية (المكان المغلق / المكان المفتوح) أنموذجاً)) - محمود, عيد; عباس, فيروز (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تشغل دراسة الثنائيات الضدية المكانية اهتمام عدد من الدراسـات النقدية الحديثة ؛ إذ راح دارسو الشـعر والنثر المعاصرون يتقصون أبعاد هذه الثنائيات الجمالية في الأعمال الأدبيـة, ويعـدُّ القاص حيدر حيدر ممن احتفت قصصهم بهذه الثنائية, وهذا ما جعل من هذه الدراسة تبحث في ثنائية ( المكان المغلق/المكان المفتوح ) بوصفها أنموذجاً للثنـائيات المكانيـة في قصصه, إذ تشـكل هذه الثنائية مرتكزاً مهماً في التعبير عن الواقع, وأزمة الإنسان المعاصر, وتقديم رؤى الكاتب, ومواقفه من العالم. The study of oppositional dualities of place occupied the interest of a number of the modern critical studies. Researchers of contemporary prose and poetry began to study the dimensions of these aesthetic dualities in the literary works. The story teller, Hidar Hidar, is considered as one of those writers interested in this duality in his stories. So this research focuses on the duality of the closed place and the open one as a standard of the dualities of place in his stories. The study forms an important basis in revealing the reality, the crisis of the modern man, and the writer’s vision as well as his opinion about the world.